2014
DOI: 10.1158/1535-7163.mct-13-0966
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Characterization of Irreversible Mutant-Selective EGFR Inhibitors That Are Wild-Type Sparing

Abstract: Patients with non-small cell lung carcinoma (NSCLC) with activating mutations in epidermal growth factor receptor (EGFR) initially respond well to the EGFR inhibitors erlotinib and gefitinib. However, all patients relapse because of the emergence of drug-resistant mutations, with T790M mutations accounting for approximately 60% of all resistance. Second-generation irreversible EGFR inhibitors are effective against T790M mutations in vitro, but retain affinity for wild-type EGFR (EGFR WT

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…Pharmacokinetic and pharmacodynamic studies in H1975 (EGFR L858R/T790M) tumor-bearing mice showed that exposure was dose proportional resulting in dose-dependent EGFR modulation. As indicated for AZD9291, this compound showed no inhibition of wild type EGFR in animals [63]. CO-1686 is currently in a phase I/II clinical trial in patients with EGFR mutated-advanced NSCLC that have received prior EGFR-directed therapy.…”
Section: T790m and Third Generation Tkimentioning
confidence: 99%
“…Pharmacokinetic and pharmacodynamic studies in H1975 (EGFR L858R/T790M) tumor-bearing mice showed that exposure was dose proportional resulting in dose-dependent EGFR modulation. As indicated for AZD9291, this compound showed no inhibition of wild type EGFR in animals [63]. CO-1686 is currently in a phase I/II clinical trial in patients with EGFR mutated-advanced NSCLC that have received prior EGFR-directed therapy.…”
Section: T790m and Third Generation Tkimentioning
confidence: 99%
“…Here, we sought to extend these initial findings by determining the proteome-wide reactivity of third-generation inhibitors for EGFR designed to selectively and irreversibly target the T790M drug-resistant mutant form of this kinase. All three inhibitors investigated – the recently approved osimertinib (Tagrisso, AZD9291; 1 , Figure 1A), PF-06747775 ( 2 , Figure 1A) and rociletinib (CO-1686; 3 , Figure 1A) – were optimized for an EGFR inhibition profile that maintained good potency against the two original drug-sensitive, kinase-activating mutants (exon19Del and L858R) and the two major drug-resistant T790M mutants (exon19Del/T790M and L858R/T790M), while showing reduced activity against wild type (WT)-EGFR to minimize mechanism-based toxicity (Cross et al, 2014, Finlay et al, 2014, Tjin Tham Sjin et al, 2014, Walter et al, 2013, Planken et al, 2017). Our chemical proteomic studies reveal that, despite the highly engineered EGFR mutant inhibition profile achieved by all three third-generation inhibitors and their shared unsubstituted acrylamide reactive group, the inhibitors exhibited strikingly distinct proteome-wide reactivity profiles in human cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The most common mechanism of resistance, accounting for 60% of cases, is the occurrence of the secondary mutation T790M (replacing a gatekeeper amino acid) in the EGFR allele harboring the TKI-sensitive mutation [5]. To overcome resistance to conventional EGFR-TKIs, a new generation of drugs (including AZD9291, CO-1686, and HM61713) that suppress the kinase activity of EGFR proteins harboring secondary T790M substitutions is currently being developed [6][7][8][9]. Phase I clinical trials demonstrate that progressed NSCLC patients who are diagnosed with T790M-positive tumors by genetic testing of rebiopsied tumor tissues respond to these new drugs [10].…”
Section: Introductionmentioning
confidence: 99%